A construção de um site educacional por alunos de um curso do ensino médio profissionalizante: contribuições para o ensino de biologia - Guerreiro, Cláudia Joelma (2015)
The identification of a strategy of active learning, characterizes the processes of participation of the pupil in the activities of the group, especially in the integration in the group and its involvement in the accomplishment of the tasks. To promote a propitious environment to the collaborative learning, we have that, initially and at least, to supply a media that makes possible the interaction, as the many presented spaces and environments to follow. Leaving of this estimated, was analyzed that when used for the education, the Technologies of the Information and Communication (TIC) use the computer and the Internet as pedagogical tools, that being a means intervene favorably in the learning process, allowing to the pupil to construct and to reconstruct their knowledge. For the accomplishment of this work, we searched to verify indications of collaborative learning in pupils of a school of Professionalizing Average Education, while they were building an educative site, using as main tool, the work in groups. The level of involvement of the participants during the process of elaboration of the apparatus was still evaluated. As research methodology it was opted to the study of case of the only type, through which by means of a deep research in a delimited object, it is possible to enter in a reality that not obtained fully for a sampling survey and exclusively quantitative evaluation. As research technique, it was chosen participant comment since to observe very aid the researcher. Their great advantage is related with the fact of the researcher to get the information in the spontaneous occurrence of the fact. In our accompaniment, it was possible to evidence that the work in groups, allowed that we established a climate of collaborative learning since these processes integrate a proposal educational in which the pupils are stimulated to work jointly in the development and construction of the knowledge. During the construction of the site, the pupils had been requested to write periodic reports regarding their difficulties and of the used means to decide the problems that had occurred throughout the process, where us were allowed to notice the importance of the team as source of socialization to know, of constructive quarrels and mutual respect. When concluding the research, we believe to have confirmed throughout the results, the objectives that we had in mind: the verification of the knowledge indications of collaborative learning, strongly marked throughout the process, as well as a great involvement of the participant students of this analysis, that could have been observed during many moments of meetings for the elaboration of the tool.